Tax noncompliance of high net-worth individuals (HNWIS) in Malaysia : perspectives of tax professionals - Natrah Saad; Abdulsalam Mas’ud; Saliza Abdul Aziz; Nor Aziah Abdul Manaf; Muhammad Aqbal Mashadi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Documented evidence has shown that a significant number of high net-worth individuals (HNWIs) whose contribution accounted for more than 11% of personal income tax collections has been caught in tax malfeasance over the period of 2009-2013 through Inland Revenue Board of Malaysia (IRBM) tax audits. Notwithstanding this, very few attempts were made to understand the noncompliance behaviour of this group of taxpayers. Therefore, this article examines the influence of probability of detection, perceived severity of punishment, political affiliation, role of tax professionals, conditional cooperation, and vertical fairness on HNWIs’ noncompliance behaviour. For this purpose, a survey was conducted on tax professionals who had been dealing with HNWIs on their tax matters. Regression analysis through Partial Least Square reveals that the probability of detection, political affiliation and role of tax professionals have a significant influence on tax noncompliance behaviour among HNWIs. It is expected that the results will be of immense benefit to IRBM in understanding the perceived determinants of HNWIs tax noncompliance in Malaysia to formulate relevant strategies.